2007
DOI: 10.1002/adfm.200700060
|View full text |Cite
|
Sign up to set email alerts
|

Soft Mechanical Sensors Through Reverse Actuation in Polypyrrole

Abstract: The phenomenon of voltage generated from a soft sensor using polypyrrole in response to mechanical deformation is described and investigated. The sensor consists of two polypyrrole layers in contact with an electrolyte and operates in bending mode in air. The magnitude and sign of the induced voltage was found to depend on the type of dopant counter‐ions and the nature of the surrounding electrolyte. The mechanical sensor response is shown to be a “reverse actuation”, generating millivolt signals for millimete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
105
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(108 citation statements)
references
References 25 publications
3
105
0
Order By: Relevance
“…For the strain at the fixed end of the sensor, x = 0. The effective modulus of elasticity E = σ/ε of the cantilever polymer sensor can be estimated using (12) and (14). For the experimental results in Fig.…”
Section: Estimation Of Sensor Outputmentioning
confidence: 99%
See 3 more Smart Citations
“…For the strain at the fixed end of the sensor, x = 0. The effective modulus of elasticity E = σ/ε of the cantilever polymer sensor can be estimated using (12) and (14). For the experimental results in Fig.…”
Section: Estimation Of Sensor Outputmentioning
confidence: 99%
“…The work most relevant to this study includes that of Takashima et al [15] and Wu et al [13], [14]. Takashima et al [15] reported on the mechanically induced current observed in polyaniline films under a tensile load, without considering the effect of dopant ions.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In the experiments of Wu et al (5) and Alici et al (6) , the electricity of the conducting polymer sensor is induced during transient responses. However, the simulation model for the transient behaviors has not been established until now.…”
Section: Introductionmentioning
confidence: 99%